2022
DOI: 10.3390/pharmaceutics15010025
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an Injectable Hydrogel Depot System for the Controlled Release of Retinal-Targeted Hybrid Nanoparticles

Abstract: A drawback in the development of treatments that can reach the retina is the presence of barriers in the eye that restrain compounds from reaching the target. Intravitreal injections hold promise for retinal delivery, but the natural defenses in the vitreous can rapidly degrade or eliminate therapeutic molecules. Injectable hydrogel implants, which act as a reservoir, can allow for long-term drug delivery with a single injection into the eye, but still suffer due to the fast clearance of the released drugs whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…The evaluation of PolySia-NPs for intravitreal administration has also been evaluated in the setting of drug delivery to the retina [ 27 , 28 , 29 , 30 ]. Fenofibrate (peroxisome proliferator-activated receptor alpha (PPAR) agonist)-encapsulated PLGA nanoparticles and blank PLGA NP were tested intravitreally in streptozocin-induced diabetic rats, laser-induced choroidal neovascularization, and very low-density lipoprotein receptor knockout (Vldlr −/−) mice, and no toxicity to retinal structure and function was noted [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of PolySia-NPs for intravitreal administration has also been evaluated in the setting of drug delivery to the retina [ 27 , 28 , 29 , 30 ]. Fenofibrate (peroxisome proliferator-activated receptor alpha (PPAR) agonist)-encapsulated PLGA nanoparticles and blank PLGA NP were tested intravitreally in streptozocin-induced diabetic rats, laser-induced choroidal neovascularization, and very low-density lipoprotein receptor knockout (Vldlr −/−) mice, and no toxicity to retinal structure and function was noted [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was also no effect on retinal function as measured by electroretinogram, like the negative findings when fenofibrate-containing nanoparticles were injected intravitreally and eyes were examined by ERG [ 31 ]. Intravitreal PLGA has been shown pre-clinically in nanoparticles and clinically in a PLGA-dexamethasone eluting implant to be safe and non-toxic [ 29 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in the eye, IVT injected fluorescently-labeled EVs were cleared from the vitreous, yet were retained in the RGCs in vivo , with a retention time between 6 and 14 days ( Mathew et al, 2021 ). A possible approach to increase the retention time of the IVT injected EVs, could be to incorporate the EVs in hydrogel implants which, by acting as reservoirs in the vitreous humor, may ensure a prolonged EV release and an increased therapeutic window with a single injection into the eye ( Ilochonwu et al, 2020 ; Ottonelli et al, 2022 ). Finally, it is still unclear which EV cargo component is responsible for the therapeutic effects observed in the above-mentioned studies, and many of them do not explore the precise cellular target.…”
Section: Discussionmentioning
confidence: 99%
“…The co-polymerization of hydrophilic and hydrophobic components is typically observed in Pluronic triblocks as well, also known as poloxamers. Pluronic F-127 (i.e., poloxamer 407) has been widely explored for IVT ocular drug delivery [ 62 , 63 , 64 , 65 ]. The triblock consists of a central hydrophobic PPG flanked on either side by hydrophilic PEG blocks [ 62 ].…”
Section: Intravitreal Drug Delivery Systemsmentioning
confidence: 99%
“…The triblock consists of a central hydrophobic PPG flanked on either side by hydrophilic PEG blocks [ 62 ]. When combined with HA, two groups have recently observed positive results, with excellent injectability, abundant localization to the retinal tissue, good cell bioavailability, and controlled release with a superior anti-angiogenic effect when compared to ranibizumab suspension over 12 weeks [ 62 , 64 ]. They also showed that drug-in-liposome-in-hydrogel delivery was an option for those drugs that are not compliant with the hydrogel properties, such as flurbiprofen, a nonsteroidal anti-inflammatory drug (NSAID) for macular edema, thus expanding potential uses [ 63 ].…”
Section: Intravitreal Drug Delivery Systemsmentioning
confidence: 99%